2015
DOI: 10.3390/v8010007
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 Is Upregulated in HTLV-1-Mediated T-Cell Transformation and Selective Inhibition Alters Viral Gene Expression and Infected Cell Survival

Abstract: Human T-cell leukemia virus type-1 (HTLV-1) is a tumorigenic retrovirus responsible for development of adult T-cell leukemia/lymphoma (ATLL). This disease manifests after a long clinical latency period of up to 2–3 decades. Two viral gene products, Tax and HBZ, have transforming properties and play a role in the pathogenic process. Genetic and epigenetic cellular changes also occur in HTLV-1-infected cells, which contribute to transformation and disease development. However, the role of cellular factors in tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 54 publications
(98 reference statements)
1
27
0
1
Order By: Relevance
“…Among PRMTs, PRMT5 appears to play a particularly relevant role in the regulation of cell death and malignant transformation processes in mouse and humans (3538). Indeed, PRMT5 is up-regulated in various human lymphoid malignancies (3941) and solid tumors (42–48) and promotes cancer cell proliferation and survival (38, 46, 49, 50). This has led to the development of selective PRMT5-inhibiting drugs such as CMP5 and EPZ015666 as a potential new therapy in cancer (43, 51, 52).…”
Section: Introductionmentioning
confidence: 99%
“…Among PRMTs, PRMT5 appears to play a particularly relevant role in the regulation of cell death and malignant transformation processes in mouse and humans (3538). Indeed, PRMT5 is up-regulated in various human lymphoid malignancies (3941) and solid tumors (42–48) and promotes cancer cell proliferation and survival (38, 46, 49, 50). This has led to the development of selective PRMT5-inhibiting drugs such as CMP5 and EPZ015666 as a potential new therapy in cancer (43, 51, 52).…”
Section: Introductionmentioning
confidence: 99%
“…They found that PRMT5 and HTLV-1 p30 had an additive inhibitory effect on HTLV-1 gene expression. However, reduced levels of PRMT5 did not significantly affect the ability of p30 to repress viral transcription, suggesting that the inhibitory role of p30 does not depend on PRMT5 [67].…”
Section: P30 Regulates Viral Latencymentioning
confidence: 88%
“…Using mass spectrometry, the arginine methyltransferase 5 (PRMT5) was recently identified as a p30 binding partner [56]. Panfil and colleagues investigated the role of PRMT5 in HTLV-1 infection and pathogenesis, showing that this cellular factor mediates cellular transformation and inhibits viral gene expression [67]. PRMT5 levels were found to be elevated in HTLV-1 transformed cells and knockdown of PRMT5 with shRNA or inhibition with a small molecule PRMT5 inhibitor increased HTLV-1 gene expression and decreased cellular proliferation and viability.…”
Section: P30 Regulates Viral Latencymentioning
confidence: 99%
“…The pLenti-puro vector expressing HA-tagged T592A and HD/RN SAMHD1 mutant constructs were generated using a Quikchange mutagenesis kit (Agilent Technologies) (27). The HTLV-1-LTR luciferase reporter plasmid and pcTax were provided by Patrick Green (The Ohio State University) (71). The HIV-1 FF-luc (pGL3-LTR-luc) was provided by Jian-Hua Wang (Pasteur Institute of Shanghai) (55).…”
Section: Methodsmentioning
confidence: 99%